2009
DOI: 10.2989/ajar.2009.8.1.6.719
|View full text |Cite
|
Sign up to set email alerts
|

Couples' communication on sexual and relational issues among the Akamba in Kenya

Abstract: A large portion of HIV transmission in sub-Saharan Africa occurs among married couples, yet the majority of research on safer-sex communication has focused on communication between couples in casual relationships. This paper explores how committed Kamba couples in Machakos District, Kenya, communicate about sensitive relational issues. The findings from focus group discussions with five groups of males and five groups of females are presented. The couples freely shared their thoughts about daily and economic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Our findings are also consistent with other spousal reports on HIV-related behavior. In Kenya, Miller and colleagues (2009) found that when husbands and wives were discordant about whether they communicated about AIDS, men were generally more likely to say “yes” while women were more likely to say “no”. Together, these results highlight the role that gender plays in reporting of HIV disclosure, suggesting that future efforts focus on addressing the issue of social desirability among men.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also consistent with other spousal reports on HIV-related behavior. In Kenya, Miller and colleagues (2009) found that when husbands and wives were discordant about whether they communicated about AIDS, men were generally more likely to say “yes” while women were more likely to say “no”. Together, these results highlight the role that gender plays in reporting of HIV disclosure, suggesting that future efforts focus on addressing the issue of social desirability among men.…”
Section: Discussionmentioning
confidence: 99%
“…Results provide support for the use of both methods, and highlight the mutual influence of partners and communication on sexual barrier use among couples in sub-Saharan Africa. 28,29 Future prevention studies should incorporate both products and partners to achieve optimal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al (2009) found that Akamba couples in Kenya sought to address sensitive issues with caution using intermediaries (such as church members, friends or family) or a circuitous approach “until the bull’s eye at the centre of their own relationship was reached” (2009: 56). Like Miller et al’s study participants, our participants used caution in addressing HIV risk in their relationships and deployed indirect strategies to draw their partners into the core issues that concerned them.…”
Section: Methodsmentioning
confidence: 99%
“…While men were often expected to initiate sexual relationships, women were generally expected to initiate discussions of HIV (cf. Miller et al 2009). As Sibongile in Vulindlela asserted,

It is not easy for a male person to think that they need to test because commonly males do not really care that much about [testing].

…”
Section: Methodsmentioning
confidence: 99%